Pendampingan Guru-Guru SMP Negeri 2 Tambang dalam Mengembangkan Materi Ajar berbasis E-Learning - Etfita, Fauzul; Ahmad, Arimuliani; Wahyuni, Sri; Satriani, Estika; Alber; Asnawi (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
As a professional educator, the teacher is expected to be able to develop their competencies. One of the competencies that must be developed is pedagogical competence. Pedagogical competence is the teacher's ability to manage learning to achieve success in the process and assessment. Currently, technological advances have supported the development of education that allows teachers to integrate conventional teaching and learning processes with e-learning. The purpose of this activity is to increase teachers' knowledge about the benefits, functions, and be able to determine the type of e-learning based media that is appropriate for the learning material. The activities are carried out through three stages, namely preparation, implementation, and evaluation. From the results of the implementation, it was found that training and mentoring in this service activity was very useful because it could increase teachers' understanding in choosing and using appropriate e-learning-based learning media to support the learning process.